Service-oriented computing – ICSOC 2018 Workshops : ADMS, ASOCA, ISYyCC, CloTS, DDBS, and NLS4IoT, Hangzhou, China, November 12-15, 2018, Revised selected papers /: ADMS, ASOCA, ISYyCC, CloTS, DDBS, and NLS4IoT, Hangzhou, China, November 12-15, 2018, Revised selected papers. (2019) - Unknown
No abstract available